Antioxidant Potential of Brown Macroalgae Padina spp. and Turbinaria spp. Collected from Elak-Elak Waters, West Lombok - Safitri, Dwi; Hanifa, Nisa Isneni; Larasati, Chandrika Eka (Jurnal Biologi Tropis, 2025)
Algae are autotrophic organisms rich in bioactive compounds, including antioxidants. Macroalgae are classified into three main groups, namely brown, red, and green algae, each possessing different pigments that influence their antioxidant activity. Previous studies have shown that brown algae such as Padina spp. and Turbinaria spp. have strong antioxidant potential. At Elak-Elak Beach, Padina spp. is found abundantly, whereas Turbinaria spp. is relatively less common, and both remain underutilized. Environmental conditions in this area are presumed to influence the phytochemical content and antioxidant activity of these algae. Therefore, this study aims to identify phytochemical compounds and evaluate the antioxidant activity of Padina spp. and Turbinaria spp. as a basis for developing sustainable algae-based products. Samples were collected during low tide, prepared as simplisia, and extracted using the ultrasonication method with 96% ethanol. Phytochemical screening was conducted using tube tests, while antioxidant activity was assessed using the DPPH method with ascorbic acid as a standard. The phytochemical test showed that both extracts were positive for flavonoids but negative for phenolics. The IC₅₀ values obtained were 3.14 ± 0.007 ppm for ascorbic acid (a very strong category), 222.27 ± 0.84 ppm for Padina spp. extract (a moderate category), and 871.84 ± 5.59 ppm for Turbinaria spp. extract (inactive category). The Kruskal–Wallis analysis indicated significant differences among groups (p = 0.027), whereas the Mann–Whitney test showed no significant difference between the IC₅₀ values of Padina spp. and Turbinaria spp. Overall, Padina spp. exhibits higher antioxidant activity and shows potential as a natural antioxidant source, while Turbinaria spp. demonstrates no antioxidant activity despite containing flavonoids.